PRACTICI DE OPTIMIZARE A PARTENERIATULUI EDUCAŢIONAL LA TREAPTA ÎNVĂŢĂMÂNTULUI PRIMAR - USM ADMIN (Moldova State University, 2010)
The educational partnership is performed permanently, together with the education itself. Planning, decision, action and evaluation in education are supposed to be implemented in cooperation between educational institutions, educational influence and educational agents. The family's actions have to comply with the school's requirements and vice versa. Primary school continues to represent the first step of the educational system that is supposed to carefully organize the child's experiences. At this level education has to be performed in close cooperation with families and the community. Educational partnership represents the way of cooperation and communication between teachers (social community) and parents, during the educational process. Cooperation between the school and the family supposes an effective and efficient communication, a range of requirements and actions in children's benefit. Nowadays, this relationship is extended through the concept of partnership that represents the expression of positive and democratic approach to education process. The partnership optimization is perceived as an improvement for all the involved parties, as a process of continuous interaction, development and reciprocal reinforcement between the school and the family.